Article Commentary: Research on the Dark Side of Personality Traits in Entrepreneurship: Observations from an Organizational Behavior Perspective - Klotz, Anthony C.; Neubaum, Donald O. (Entrepreneurship Theory and Practice, 2016)
While the personality of entrepreneurs can be cast in positive and negative lights, it is essential that researchers understand the complex process through which personalities shape behavior and influence outcomes. Building on Miller's observations on downsides of entrepreneurs’ personalities, we present five broad lines of inquiry derived from the organizational behavior literature to guide future research on the role of personality in entrepreneurial phenomena. These streams of research have implications for how personality is conceptualized in the entrepreneurship literature, and we urge researchers to examine interactions among different personality traits, and between traits and contextual and affective variables which play a critical role in personality–outcome relationships. Finally, we encourage scholars to consider the personality of new venture team members, and how some traits may serve important resource–conservation roles.